(untitled) (Research, Society and Development, 2022)
The pregnancy-specific hypertensive syndrome (PSHS) is one of the main causes of maternal-fetal mortality. The professional who establishes a bond with the pregnant woman and monitors prenatal, childbirth and postpartum care must know the risk factors that affect the health of the woman and the baby, allowing the planning of care aimed at preventing complications. The aim of this study is to identify the risk factors, complications and the nursing performance in PSHS and to list the main diagnoses, goals and nursing interventions. This is a systematic review, whose sample was composed of 14 articles. A profile of the pregnant woman most at risk for the onset of PSHS was then outlined, and characteristics such as maternal age, socioeconomic conditions, level of education, ethnicity, personal and family history, and obstetric history were defined. Maternal and perinatal complications were identified. The nursing performance is evidenced by early detection actions, evaluation of risk factors, and encouragement of therapeutic adherence. Furthermore, diagnosis, goals, and nursing interventions operationalize care in PSHS. Although the number of publications is scarce, the study considers clear in the literature the description of risk factors for the emergence of PSHS and its main complications. These aspects are the basis for the nursing performance that will work in the identification of these risk factors, monitoring of signs and symptoms, prevention of diseases, and welcoming pregnant women and their families.